Boron fertilization effects in processing grade potato on an Inceptisol of West Bengal, India. (3rd July 2018) - Sarkar, Sukamal; Banerjee, Hirak; Ray, Krishnendu; Ghosh, Dibakar
ABSTRACT: A 2-year field trial was conducted in processing grade potato cv. Kufri Chipsona-3. The treatments comprised recommended dose of fertilizer (RDF) (200:150:150 N:P2 O5 :K2 O kg ha −1 ) with or without boron (B) application (soil and foliar). The results revealed that B fertilization significantly increased tuber number and yield. Three sprays of 0.1% boric acid (at 40, 50 and 60 days after planting) produced the maximum number and yield of tubers and enhanced B uptake in potato tuber, haulm as well as in total plant accounting 85.8, 182.0 and 169.8% more than control, respectively. The same treatment came up with greatest net return and benefit: cost ratio. B fertilization exerted significant influence on available N and B status of post-harvest soil, while the effect was non-significant on available P and K. Results suggest that right dose and method of B application is vital for optimizing tuber yield and B-use efficiency for processing grade potato.